2014
DOI: 10.1007/s12011-014-9983-x
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Blood Mg2+ and Energy Metabolites/Enzymes After Acute Exhaustive Swimming Exercise in Rats

Abstract: Magnesium (Mg) plays a central role in neuronal activity, cardiac excitability, neuromuscular transmission, muscular contraction, vasomotor tone, and blood pressure, all of which are significantly related to physical performance. To date, the available data about detection of blood total Mg (tMg; free-ionized, protein-bound, and anion-complex forms) are inconsistent, and there is limited information on blood free-ionized Mg (Mg(2+)) in relation to physical exercise. The aim of this study was to determine the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 29 publications
2
15
0
Order By: Relevance
“…Also as expected, the serum CRE, BUN, and UA levels were significantly increased in diabetic rats as a consequence of renal failure, extracellular dehydration, and protein catabolism, respectively [ 1 , 17 ]. In contrast, the treated groups exhibited significantly reduced levels of these indicators, suggesting that allation, yam powder, and its aqueous extract can all improve renal function, prevent extracellular dehydration, and avoid protein catabolism.…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…Also as expected, the serum CRE, BUN, and UA levels were significantly increased in diabetic rats as a consequence of renal failure, extracellular dehydration, and protein catabolism, respectively [ 1 , 17 ]. In contrast, the treated groups exhibited significantly reduced levels of these indicators, suggesting that allation, yam powder, and its aqueous extract can all improve renal function, prevent extracellular dehydration, and avoid protein catabolism.…”
Section: Discussionsupporting
confidence: 57%
“…As with other symptoms, all the treatments reduced these effects, indicating that they promote the proper utilization of glucose thereby ameliorating ketosis. The increased blood Osm in the diabetic group may result from the elevated blood glucose and BUN levels [ 17 , 32 ]. Alternatively, it may result from insulin deficiency [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…rhabdomyolysis produced by toxins from venom). When these cells are damaged, the cytosolic enzymes, including ALT, AST, LDH and CK, leak out into the circulating blood and exceed normal values [ 15 ]. Other studies have shown that, within a few hr of bee envenomation, serum ALT, AST and CK levels are significantly elevated in horses [ 11 ] and mice [ 14 ], indicating acute liver injury.…”
mentioning
confidence: 99%